'You have said things you should not have said': Trauma, healing, and treacherous self-telling in stories of Haitian women. Issue 1 (August 2015) - Glover, Kaiama L.
Abstract : This article is focused on a series of texts written in and about Haiti and circulated throughout the literary and cyber spaces of the global 'First World'. It takes as its point of departure Edwidge Danticat's intervention into a 'post-earthquake' debate among women researchers and journalists regarding the representation of Haiti and, especially, women living in the tent cities. The article considers the geo-political borders that circumscribe the bodies and the voices of the most marginalized. Tracing the path from the actual to the fictional and back, this article moves from a real-world controversy around the particular, involuntarily public trauma of one Haitian rape survivor to a consideration of the ethics of storytelling in a hierarchically raced and gendered world.